2017
DOI: 10.1111/nin.12228
|View full text |Cite
|
Sign up to set email alerts
|

‘Holding on to life’: An ethnographic study of living well at home in old age

Abstract: In recent years, much attention has been paid to how older people living at home can remain independent and manage their illness themselves, while less attention has been given to those who have become frail and need assistance with challenges of everyday life. In this article, I drew on Latimer's formulation of care for frail older people as relational and world-making and on Foucault's work related to the care of the self in developing an understanding of how frail older persons manage to live well at home i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(41 citation statements)
references
References 40 publications
2
39
0
Order By: Relevance
“…Reduced vision was annoying when it made reading the newspaper difficult or when they had to ask for help with changing light bulbs or other simple practical everyday tasks. Such findings concur with previous reports on how hearing and vision impairments affect everyday competencies (Tiwana, Benbow, & Kingston, ; Bjørnsdottir, ). Hearing impairment in particular is a burden in social life, while vision impairment strongly impacts everyday competencies (Heyl & Wahl, ).…”
Section: Discussionsupporting
confidence: 92%
“…Reduced vision was annoying when it made reading the newspaper difficult or when they had to ask for help with changing light bulbs or other simple practical everyday tasks. Such findings concur with previous reports on how hearing and vision impairments affect everyday competencies (Tiwana, Benbow, & Kingston, ; Bjørnsdottir, ). Hearing impairment in particular is a burden in social life, while vision impairment strongly impacts everyday competencies (Heyl & Wahl, ).…”
Section: Discussionsupporting
confidence: 92%
“…They also actively provided it to others. This finding overlaps with the concepts of “vitality and agency in frailty” for preserving self-identity and continued self-development in later life ( Bjornsdottir, 2018 ; Latimer, 2012 ). It also highlights the crucial role of opportunities for social participation, meaningful and reciprocal contribution, and relationship building to aging in place.…”
Section: Discussionsupporting
confidence: 50%
“…This theme represents the external perception and selfperception of aged persons within care relationships. While most of these people had to deal with physical and mental deteriorations such as diminished vision and, consequently, restrictions such as loss of mobility, they focused on the remaining options available to them-they wanted to enjoy their lives despite their old age (Behm et al 2013;Bjornsdottir 2018;Faeo et al 2020;Moe et al 2013;Spoorenberg et al 2015). The primary studies showed that older people wanted to be seen and accepted as valuable individuals who still act on their own, take pleasure in daily activities and contribute something to society (Behm et al 2013;Krothe 1992;Martin-Matthews and Sims-Gould 2008;Moe et al 2013;Tiilikainen et al 2019;Toien et al 2015).…”
Section: Feeling Like a Meaningful Human Beingmentioning
confidence: 99%
“…More explicitly, experiencing friendliness and respect made older people feel valuable, while experiencing rudeness and disrespect made them feel burdensome and unimportant (Bjornsdottir 2018;Jarling et al 2018;Moe et al 2013;Soodeen et al 2007;Toien et al 2015). Such negative care relationship experiences inhibited open communication between the older persons and their healthcare providers (Jarling et al 2018;Moe et al 2013).…”
Section: Feeling Like a Meaningful Human Beingmentioning
confidence: 99%
See 1 more Smart Citation